1997
DOI: 10.1111/1523-1747.ep12335801
|View full text |Cite
|
Sign up to set email alerts
|

Increased Sensitivity to Peroxidative Agents as a Possible Pathogenic Factor of Melanocyte Damage in Vitiligo

Abstract: To examine the sensitivity of vitiligo melanocytes to external oxidative stress, we studied enzymatic and non-enzymatic anti-oxidants in cultured melanocytes of normal subjects (n = 20) and melanocytes from apparently normal skin of vitiligo patients (n = 10). The activity of superoxide dismutase and catalase and the intracellular concentrations of vitamin E and ubiquinone were evaluated in cultures at the fourth or fifth passage. In addition, cells were exposed to various concentrations of a peroxidizing agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
253
1
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(283 citation statements)
references
References 19 publications
17
253
1
4
Order By: Relevance
“…The vacuolation and degenerative changes noted in NSV skin could be the expression of oxidative damage (51,52). Low catalase activity leading to epidermal accumulation of H 2 O 2 has been demonstrated in non-lesional and in lesional NSV skin (53) and in cultured melanocytes (54,55). Accumulation of H 2 O 2 in NSV skin in vivo has been shown (56).…”
Section: Melanocyte Destructionmentioning
confidence: 98%
“…The vacuolation and degenerative changes noted in NSV skin could be the expression of oxidative damage (51,52). Low catalase activity leading to epidermal accumulation of H 2 O 2 has been demonstrated in non-lesional and in lesional NSV skin (53) and in cultured melanocytes (54,55). Accumulation of H 2 O 2 in NSV skin in vivo has been shown (56).…”
Section: Melanocyte Destructionmentioning
confidence: 98%
“…However, the early death of vitiligo melanocytes was shown to be provoked by their increased sensitivity to oxidative stress, impacting tyrosinase activity and eumelanin synthesis [51,52]. It was also demonstrated that there were very high levels of H 2 O 2 and concomitant reduced activity of catalase in the epidermis of patients with vitiligo [53], reducing the levels of methionine sulfoxide reductase A and B and thioredoxin/thioredoxin reductase which triggers oxidative stress, As it was seen, during the process of melanogenesis, oxidative insults responsible for melanocyte damage can be caused not only by various ROS, namely H 2 O 2 , hydroxyl radicals and superoxide anion, but also by intermediates in melanin synthesis.…”
Section: Vitiligomentioning
confidence: 99%
“…The absence of melanocytes in the skin lesions was previously reported to be the key event in the pathogenesis of vitiligo (2); however, the aetiology of vitiligo remains to be elucidated. Previous studies have suggested that oxidative stress may result in the loss of melanocytes (3,4); increased intracellular reactive oxygen species (ROS) production was observed in the epidermis of vitiligo patients (5), which therefore indicates the presences of systemic oxidative stress in vitiligo (6,7). Accumulated oxidative stress leads to DNA damage, lipid and protein peroxidation and cell death (8,9).…”
Section: Introductionmentioning
confidence: 99%